2020
DOI: 10.21203/rs.3.rs-43681/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birth preparedness and complication readiness among women of reproductive age in Kenya and Tanzania: a community-based cross-sectional survey

Abstract: Introduction: Delayed health-seeking continues to contribute to preventable maternal and neonatal deaths in low resource countries. Some of the strategies to avoid the delay include early preparation for the birth and detection of danger signs. We aimed to assess the level of practice and factors associated with birth preparedness and complication readiness (BPCR) in Kenya and Tanzania.Methods: We conducted community-based multi-stage cross-sectional surveys in Kilifi and Kisii counties in Kenya and Mwanza reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was also a surprising but important finding that being single had positive influence on preparation of money and food as well as preference of SBA. Several studies showed opposite results that being single had negative influence on preparedness [ 30 32 ]. For example, a study in Ethiopia revealed that being single was one of the significant predictors of unplanned home delivery [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also a surprising but important finding that being single had positive influence on preparation of money and food as well as preference of SBA. Several studies showed opposite results that being single had negative influence on preparedness [ 30 32 ]. For example, a study in Ethiopia revealed that being single was one of the significant predictors of unplanned home delivery [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because, most pregnancy complications occur during delivery and can result in poor pregnancy outcomes (41) which can result into mis-interpretation of safety outcomes of a maternal vaccine. In a survey to nd out birth preparedness and complication readiness among Kenyan women showed only 11.4% (59/519) were well prepared for births and its complications during pregnancy (42). Initiatives such as provision of night transport services to pregnant women during labour, equipping lower levels health facilities with quali ed staff, training, oversight and resources to handle emergencies which will encourage pregnant women utilize hospital services to reduce risks associated with home deliveries, will be reasonable, but should not be a barrier to vaccine rollout.…”
Section: Discussionmentioning
confidence: 99%